2020
DOI: 10.1111/1541-4329.12200
|View full text |Cite
|
Sign up to set email alerts
|

Survey analysis of computer science, food science, and cybersecurity skills and coursework of undergraduate and graduate students interested in food safety

Abstract: Automation is coming and will enable not only the ability to increase poultry processing line speeds, but also the collection of considerable "big data." These data can be collected en masse, stored, analyzed, and used to improve food safety, quality, enhance traceability, and also be used for risk assessment. However, as this technology is implemented in the poultry industry, computer hackers will emerge to pose a clear and present danger to the poultry industry and the upcoming generation of professionals mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Therefore, Thompson et al (2017) have pointed out that cybersecurity infrastructure in the food and poultry industries will become a critical issue for education and training. When Feye et al (2020b) surveyed food science students for background in computer. technology and cybersecurity topics, they concluded that students were relatively deficient in these skills Feye et al (2020b) suggested that more specialized coursework needed to be devoted to not only the technological aspects of topics such as microbiome sequencing, but also data management and security to appropriately train the next generation of food and poultry science professionals and workforce members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Thompson et al (2017) have pointed out that cybersecurity infrastructure in the food and poultry industries will become a critical issue for education and training. When Feye et al (2020b) surveyed food science students for background in computer. technology and cybersecurity topics, they concluded that students were relatively deficient in these skills Feye et al (2020b) suggested that more specialized coursework needed to be devoted to not only the technological aspects of topics such as microbiome sequencing, but also data management and security to appropriately train the next generation of food and poultry science professionals and workforce members.…”
Section: Discussionmentioning
confidence: 99%
“…When Feye et al (2020b) surveyed food science students for background in computer. technology and cybersecurity topics, they concluded that students were relatively deficient in these skills Feye et al (2020b) suggested that more specialized coursework needed to be devoted to not only the technological aspects of topics such as microbiome sequencing, but also data management and security to appropriately train the next generation of food and poultry science professionals and workforce members. This holds true for current poultry and allied industry personnel as well.…”
Section: Discussionmentioning
confidence: 99%
“…While it might be assumed that incoming college students are somewhat aware of digital technologies, how extensive their background is unclear. In a survey of undergraduate and graduate students interested in food safety, Feye et al (2020c) concluded that students were aware of some digital venues such as social media and word processing software, but much less so for digital technologies associated with web design and cybersecurity. Not surprisingly, Martins et al (2020) observed similar lack of familiarity in high school students with the terminology and definition of bioinformatics.…”
Section: Agricultural Education and Nonconventional Poultry Producersmentioning
confidence: 99%
“…Not surprisingly, Martins et al (2020) observed similar lack of familiarity in high school students with the terminology and definition of bioinformatics. To remedy these deficiencies, Feye et al (2020c) suggested developing more cross disciplinary curricula that combine elements of practical agriculture sciences with computer and cybersecurity topics. These interfaces will become particularly important for adaptation of monitoring and data gathering based on microbiome bioinformatic interpretations by industries such as those with poultry processing facilities ( Feye et al, 2020b , c ).…”
Section: Agricultural Education and Nonconventional Poultry Producersmentioning
confidence: 99%
See 1 more Smart Citation